The relation between a sense of meaning in life and suicide potential among disadvantaged adolescent girls - Aviad-Wilchek, Y. (International journal of offender therapy and comparative criminology, 2018)
The study examines the influence of the sense of meaning in life, or its absence, on the suicide potential of disadvantaged adolescent girls in Israel who reside in boarding school (n = 50) compared with adolescent girls in a rehabilitation project (n = 31), and between them and normative adolescent girls (n = 128). The research findings indicate a negative relation between meaning in life and suicide potential, which exists only among the normative adolescent girls and the disadvantaged adolescent girls residing in the boarding school. This relation does not exist among the disadvantaged adolescent girls in the rehabilitation project. The explanation for this unusual finding is, apparently, the early stage of rehabilitation at which the adolescent girls are found. In conclusion, this study joins previous studies that propose prevention, intervention, and therapy programs based on increasing adolescent (disadvantaged and not disadvantaged) strength factors by finding meaning to their lives.